2021
DOI: 10.3389/fimmu.2021.620238
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 Promotes NLRP3 Inflammasome Activation by Phosphorylation of p38 MAPK Pathway in Septic Shock

Abstract: Pin1 is the only known peptidyl-prolyl cis-trans isomerase (PPIase) that can specifically recognize and isomerize the phosphorylated Serine/Threonine-Proline (pSer/Thr-Pro) motif, change the conformation of proteins through protein phosphorylation, thus regulate various cellular processes in the body. Pin1 plays an important role in cancer, Alzheimer’s disease, and autoimmune diseases. However, the specific mechanism of Pin1 regulation in LPS-induced septic shock is unclear. Here, we found that lack of Pin1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…It has been reported that the p38 MAPK pathway is closely related to LPS-induced septic shock ( 90 ). A recent study demonstrated that activation of the p38 MAPK pathway promotes NLRP3 inflammasome activation in septic shock ( 91 ). Ang II has been shown to induce NLRP3, in various cardiac cells in a non-septic cardiac damage model, depending on the AT1R/NF-κB or p38 MAPK pathway or crosstalk among them ( 76 , 77 , 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the p38 MAPK pathway is closely related to LPS-induced septic shock ( 90 ). A recent study demonstrated that activation of the p38 MAPK pathway promotes NLRP3 inflammasome activation in septic shock ( 91 ). Ang II has been shown to induce NLRP3, in various cardiac cells in a non-septic cardiac damage model, depending on the AT1R/NF-κB or p38 MAPK pathway or crosstalk among them ( 76 , 77 , 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…Coimmunoprecipitation analysis showed that Pin1 could bind to p-p38, which implied that the p-p38 MAPK might be a substrate of Pin1. Then, with GST pulldown experiment, it showed that Pin1 could not directly bind to p-p38 MAPK in vitro, suggesting that Pin1 might affect p38 MAPK through kinases or other proteins [ 27 ]. In this study, we found that the activation of p38 MAPK was induced by I/R injury and inhibition of Pin1 could suppress p38 MAPK activation in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of high ROS levels, TXNIP has been shown to quickly bind inflammasomes and trigger the assembly of inflammasomes (31). Furthermore, phosphorylation of MAPK has been proposed to upregulate transcription of the inflammasome components (32). Therefore, the effects of IL-35 on p38 MAPK and TXNIP expression was examined in bEnd.3 cells subjected to OGD/R.…”
Section: Il-35 Suppressed the Production Of Ros In Ogd/r-induced Bend...mentioning
confidence: 99%